2023
DOI: 10.59287/ijanser.717
|View full text |Cite
|
Sign up to set email alerts
|

Digital tools in education

Daniel Dancsa,
Iveta Štempeľová,
Ondrej Takáč
et al.

Abstract: Over the past decades, the demands placed on education systems have changed. Workers in the labour market need certain competences such as technical, methodological, social and personal competences. The aim of education today is to create a new educational paradigm that prepares the workforce of the future for the new challenges. This change is accompanied by the introduction of new didactic concepts such as blended learning, which combines the advantages of face-to-face and online learning with the use of dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The effectiveness of digital assessments largely depends on the readiness of the digital educational environment, the level of digital literacy and the competence of the academic staff who assess the learners (Mitrofanova et al, 2020). According to Dancsa et al (2023), online digital tools are software, applications, technologies, plug-ins, add-ons or websites that are accessible via an internet connection and enhance learners' ability to master the knowledge they need to learn. These include LMS and digital assessment tools.…”
Section: B) Digital Preparednessmentioning
confidence: 99%
“…The effectiveness of digital assessments largely depends on the readiness of the digital educational environment, the level of digital literacy and the competence of the academic staff who assess the learners (Mitrofanova et al, 2020). According to Dancsa et al (2023), online digital tools are software, applications, technologies, plug-ins, add-ons or websites that are accessible via an internet connection and enhance learners' ability to master the knowledge they need to learn. These include LMS and digital assessment tools.…”
Section: B) Digital Preparednessmentioning
confidence: 99%
“…Since then, digital literacy training has become teachers' global professional development component. Several scholars have reported that the integration of digital tools and resources into teaching methodologies has become essential to meet the evolving needs of 21st-century learners (Bondarenko & Gudkova, 2023;Dancsa et al, 2023;Hafeez, 2021;McWhorter, 2021;Nikolova & Evtimova, 2022;Ng et al, 2022;Shuhidan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%